Масофавий курсларни ташкил этишда дастлабки таҳлил ўтказиш самарадорликни таъминлашнинг муҳим омили сифатида (SCIENCE and SOCIETY, 2020)
This article highlights the importance of preliminary analysis for the organization of distance learning courses and the distinctive as- pects of the audience of students in the system of lifelong education, the peculiar features of the development of the content of distance learning courses, taking into account precisely these differences, choice, effective implementation of learning technologies into practice.